Void moon ebook - Connelly, Michael (2001)
New York Times bestselling author Michael Connelly writes novels of brilliantly original suspense. In this electrifying tour de force, he takes us into a world of extremes: too much criminality, too much money, and too many ways to die. In L.A. Cassie Black is another beautiful woman in a Porsche: except Cassie just did six years in prison and still has "outlaw juice" flowing in her veins. Now Cassie is returning to her old profession, taking down a money man in Vegas. But the perfect heist goes very wrong, and suddenly Cassie is on the run—with a near-psychotic Vegas "fixer" killing everyone who knew about the job. Between Cassie and the man hunting her are a few last secrets: like who really set up the job, why Cassie had to take the change, and how, in the end, it might all be a matter of the moon...